2017
DOI: 10.1101/105502
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extensive Copy Number Variation in Fermentation-Related Genes amongSaccharomyces cerevisiaeWine Strains

Abstract: Due to the importance of Saccharomyces cerevisiae in wine-making, the genomic variation of wine yeast strains has been extensively studied. One of the major insights stemming from these studies is that wine yeast strains harbor low levels of genetic diversity in the form of single nucleotide polymorphisms (SNPs). Genomic structural variants, such as copy number (CN) variants, are another major type of variation segregating in natural populations. To test whether genetic diversity in CN variation is also low ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 98 publications
0
16
0
Order By: Relevance
“…The genomic context illustrates further parallels to evolution in Saccharomyces. The invertases are shown to reside within sub-telomeres, which are genomic regions that have been shown to be hotspots for structural rearrangements and HGT events in Saccharomyces [59][60][61][62][63]. Sucrose utilization likely conferred a significant advantage in fruit fermentations, helping to shape the evolution of the common ancestor of B. bruxellensis and B. anomalus towards this fermentation specialization.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic context illustrates further parallels to evolution in Saccharomyces. The invertases are shown to reside within sub-telomeres, which are genomic regions that have been shown to be hotspots for structural rearrangements and HGT events in Saccharomyces [59][60][61][62][63]. Sucrose utilization likely conferred a significant advantage in fruit fermentations, helping to shape the evolution of the common ancestor of B. bruxellensis and B. anomalus towards this fermentation specialization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the analysis of gene expression, single nucleotide polymorphisms (SNPs), and insertions/deletions (InDels) [ 21 , 23 , 27 , 28 ], copy number variations (CNVs) have been highlighted as a new and significant source of genetic polymorphism that contributes to phenotypic diversity such as virulence in diverse fungal species [ 29 ]. In fact, the contribution of CNVs to population genetic and phenotypic diversity has been exemplified by a range of fungal studies, including studies on yeast Saccharomyces cerevisiae (Ascomycota, Saccharomycetes) [ 30 , 31 ], the wheat pathogen Zymoseptoria tritici (Ascomycota, Dothideomycetes) [ 32 ], and the human fungal pathogen Cryptococcus deuterogattii (Basidiomycota, Tremellomycetes) [ 33 ]. It has also been noted that the degree of CNV in fungal populations is not always correlated with the degree of SNP variation, which indicated that CNV analysis could reveal an important yet hidden layer of genetic information independent of SNPs/InDels.…”
Section: Introductionmentioning
confidence: 99%
“…Saccharomyces uvarum is a striking example of a yeast species whose genome is strongly shaped by introgressed regions (Almeida et al, ). S. uvarum shares partially overlapping ecological niches with S. cerevisiae : both are strongly related to human‐driven fermentation, but S. uvarum is more psychrotrophic and thus is more frequently associated with low‐temperature processes: cider‐making and winemaking in northern – cooler – French vineyards for example (Masneuf‐Pomarede et al, ; Tosi et al, ; Demuyter et al, ; Naumov et al, ). Isolates from natural environments (insect, plant, soil) have also been described (Sampaio & Gonçalves, ; Boynton & Greig, ).…”
Section: Introductionmentioning
confidence: 99%